2018
DOI: 10.1002/cche.10079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breadmaking process on mycotoxin content in white and whole wheat breads

Abstract: Background and objectives Fusarium graminearum may reduce the wheat flour yield, technological quality, and breadmaking performance. The objective was to evaluate the effect of breadmaking on the mycotoxin content in white and whole wheat breads to obtain information about the safety of wheat products. The wheat samples were contaminated via the addition of Fusarium‐damaged kernels to produce different levels of deoxynivalenol (DON), ranging from <500 to >5,000 μg/kg. Findings Because of the breadmaking proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Nonetheless, Tibola et al. (2018) have shown that DON levels are reduced in significant percentages (39% and 49%) in final breads when comparing with both WWF and refined flours. To further reduce the presence of these toxins, it may be interesting to increase baking times or temperatures (Vidal, Sanchis, Ramos, & Marín, 2015).…”
Section: Inconveniences Of Wwf Consumptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, Tibola et al. (2018) have shown that DON levels are reduced in significant percentages (39% and 49%) in final breads when comparing with both WWF and refined flours. To further reduce the presence of these toxins, it may be interesting to increase baking times or temperatures (Vidal, Sanchis, Ramos, & Marín, 2015).…”
Section: Inconveniences Of Wwf Consumptionmentioning
confidence: 98%
“…It has also been proved that the usage of common enzymes (such as xylanases and amylases) in bread-making processes can increase DON levels in the obtained breads (Vidal, Sanchis, Ramos, & Marín, 2017). Nonetheless, Tibola et al (2018) have shown that DON levels are reduced in significant percentages (39% and 49%) in final breads when comparing with both WWF and refined flours. To further reduce the presence of these toxins, it may be interesting to increase baking times or temperatures (Vidal, Sanchis, Ramos, & Marín, 2015).…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Thus, mycotoxins can contaminate a variety of foodstuffs, such as grain-based products (wheat, oats, barley, maize, and rye), nuts, dried fruits, spices, cocoa, coffee, beer, wine, fruits, meat, and animal products (eggs, milk, and cheese) [ 14 , 46 , 47 , 48 , 49 , 50 ]. Some mycotoxins are thermostable, allowing them to endure most food processes [ 51 ]. DON is stable up to 120–180 °C and was degraded after 40 min at 210 °C [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…For ZEA, heat treatment at temperatures up to 160 °C had no significant effect and 85% reduction of the toxin concentration in barley flours was achieved after 60 min at 220 °C [ 53 ]. DON content in whole and white breads decreased by 49% and 39%, respectively, compared to the original flours [ 51 ]. According to Generotti et al [ 54 ], increasing pH and baking time in an acceptable technological range can reduce DON concentration in the final product [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation